The altrations of mast cells and goblet cells in sheep livers associated with Dicrocoelium dendriticum (Journal of Hama University, 2024)
This research aims to study the changes of mast cells and goblet cells in the hepatic bile ducts affected by Dicrocoelium dendriticum. Tissue samples were taken from 30 infected livers of sheep, and fixed in neutral formalin 10%. Histological paraffin sections) were made (4 micron thickness and stained with hematoxylin and eosin for general study, methylene-blue to detect mast cells and PAS regent to detect goblet cells.A clear increase of mast cells account was observed in the surrounding connective tissue of bile ducts, it was associated with acute cholangitis, accompanied by eosinophilic cells infiltration predominantly during this stage, while no significant increase of mast cells account was observed during chronic cholangitis.Severe to moderate hyperplasia in goblet cells of bile ducts mucosa was reported during the chronic inflammatory phase. Obvious fibrosis was found in the bile ducts wall, accompanied with infiltration of lymphocytes, plasma cells, and macrophages.It can be concluded that mast cells play an important role in early liver injury with dicrocoeliasis. While hyperplasia in goblet cells was observed associated with an increase in their secretory activity in the chronic inflammatory phase due to continuous irritation of liver flukes for bile ducts the mucous.